Managing a veterinary practice - Back, Caroline Jevring; Back, erik (Edinburgh : Saunders Elsevier, 2007)
Good management is essential to the success of every veterinary practice. This edition contains information on leadership, the role of a manager, basic financial management, marketing, communication within the practice, and how to achieve good client compliance. It also explains the core principles involved in running a business.
Keywords: Veterinary Medicine; Animal hospitals